A CMOS Hall-Effect Sensor for the Characterization and Detection of Magnetic Nanoparticles for Biomedical Applications - Liu, Paul (2011)
A CMOS Hall-effect sensor chip designed for the characterization and detection of magnetic nanoparticles (MNPs) achieves over three orders of magnitude better temporal resolution than prior solutions based on superconducting quantum interference devices and fluxgate sensors. The sensor relies on wires embedded in the chip to generate a local magnetizing field that is switched OFF rapidly to observe the relaxation field of the MNPs. The CMOS sensor chip, with integrated high-speed readout electronics, occupies 6.25 mm(2). It can be easily integrated with microfluidics and is suitable for lab-on-a-chip and point-of-care applications.